Analisis Framing Pemberitaan Gagal Ginjal Akut di Channel Youtube Kompas TV, TV One News dan CNN Indonesia - Ilham Setyawan; Feri Johansah; Aru Prayogi; Arrum Dara Efda (Mahesa Research Center, 2023)
Cases of acute kidney failure that occur in Indonesia are increasingly worrying, based on data this case has spread to 27 provinces in Indonesia. Many media have also reported on the case from different points of view and perspectives. This study aims to determine the framing of news coverage regarding cases of acute kidney failure on three Youtube Channels on October 20, 2022. The method used is Robert N. Entman's framing analysis with a qualitative approach. This study concludes that the Define Problem in the news is the use of liquid medicines or syrups that contain harmful substances is the main problem. . parents should be vigilant and careful in using drugs except on a doctor's recommendation. Treatment recommendations, the importance of the collaboration of all parties, both government, health workers, doctors and parents in the use of drugs whose ingredients are unclear. Youtube is an educational medium for the community, so the information that is reported must fulfill the principle of benefit.